2020
DOI: 10.1183/23120541.00023-2020
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical methods of measurement of respiratory rate give imprecise values

Abstract: BackgroundRespiratory rate is a basic clinical measurement used for illness assessment. Errors in measuring respiratory rate are attributed to observer and equipment problems. Previous studies commonly report rate differences ranging from 2 to 6 breaths·min−1 between observers.MethodsTo study why repeated observations should vary so much, we conducted a virtual experiment, using continuous recordings of breathing from acutely ill patients. These records allowed each breathing cycle to be precisely timed. We ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 34 publications
2
32
0
1
Order By: Relevance
“…A previous analysis of the nasal cannula signals obtained from this study showed that repeated estimates of respiratory rate, made from the same record, but at different times, could vary substantially. [6] The performance after signal selection is superior to results reported in previous studies. [11-13, 24, 25] The study has several strengths: a medically appropriate cohort of patients, studied in clinical circumstances, using an appropriate and accurate comparison signal.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…A previous analysis of the nasal cannula signals obtained from this study showed that repeated estimates of respiratory rate, made from the same record, but at different times, could vary substantially. [6] The performance after signal selection is superior to results reported in previous studies. [11-13, 24, 25] The study has several strengths: a medically appropriate cohort of patients, studied in clinical circumstances, using an appropriate and accurate comparison signal.…”
Section: Discussionmentioning
confidence: 62%
“…Ischaemic heart disease or venous thromboembolism was suspected in 14 patients, and 13 had either sepsis or urinary tract infection. The remainder had neurological conditions such as stroke (9), gastrointestinal disease (6), and other conditions (4). Many patients had comorbid conditions: these were cardiovascular in 32, respiratory in 20, diabetes in 11, and renal impairment in 12.…”
Section: Clinical Informationmentioning
confidence: 99%
See 3 more Smart Citations